2018
DOI: 10.1111/jcpe.12897
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study on the accuracy of free‐handed, pilot‐drill guided and fully guided implant surgery in partially edentulous patients

Abstract: When perfect implant positioning is required, FG surgery should be considered the gold standard approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
190
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(225 citation statements)
references
References 35 publications
12
190
0
2
Order By: Relevance
“…Fr. Similar clinical studies conducted with static guides and in partial edentulousness reported 6.99° (Younes et al, 2018) and 9.8° (Nickenig et al, 2010). In our study, Pi yielded a mean AD of 5.71°, comparable to the 5.95° reported in the study of Younes et al (2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Fr. Similar clinical studies conducted with static guides and in partial edentulousness reported 6.99° (Younes et al, 2018) and 9.8° (Nickenig et al, 2010). In our study, Pi yielded a mean AD of 5.71°, comparable to the 5.95° reported in the study of Younes et al (2018).…”
Section: Discussionsupporting
confidence: 88%
“…Dynamic systems offer real-time visualization during surgery, but their accuracy is lower than that of static systems (Jung et al, 2009). Furthermore, they are expensive and occupy considerable space (Younes et al, 2018), and their use is not always straightforward (Jorba-Garcia, Figueiredo, Gonzalez-Barnadas, Camps-Font, & Valmaseda-Castellon, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of guided implant surgery have been amply discussed in the dental literature. Higher accuracy is achievable with FG and PG guided surgery compared to FH surgery (Younes et al, ), which translates in a more correct implant positioning and thus lower risk of biological and/or technical complications (Canullo et al, ; Cassetta et al, ; Jacobs et al, ). Other benefits may be a lower morbidity due to the possibility of a flapless and thus less invasive surgery, a shorter treatment time and a better understanding of both the pre‐operative surgical site and the eventual prosthetic outcome (Buser et al, ; Ruppin et al, ; Tahmaseb et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge however, this is the first cost-effectiveness analysis on guided implant surgery. Although the clinical effectiveness of guided surgery has been widely described (Ersoy, Turkyilmaz, Ozan, & McGlumphy, 2008;Ozan et al, 2009;Schneider, Marquardt, Zwahlen, & Jung, 2009;Tahmaseb et al, 2014;Vercruyssen et al, 2014;Younes et al, 2018), no studies have addressed the question if the advantages of guided surgery outweigh the additional cost or not. For FG surgery, 10% extra operational cost is needed to reduce the AGD by 54% when compared to FH surgery.…”
Section: Discussionmentioning
confidence: 99%